Exploring Multilingualism in Professional Context: Scientometric Analysis - Lichman Е.Ю. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article examines the manifestation of psychologism when A.S. Pushkin created the image of the protagonist in the novel Evgeny Onegin. The preservation of the same method by the Kazakh classic Abay when translating the excerpts Tatyana’s Letter to Onegin, Onegin’s Letter to Tatyana from the novel into the Kazakh language is considered. The creative translation by a foreign poet is supplemented by his own version of the vision of the end of the life path of the Pushkin hero from the novel in verse. Kazakh poet created Onegin’s Dying Letter. This is absent in the plot of Pushkin’s original. Motivated by the creation of a variant of Onegin’s Dying Letter by Abai Kunanbaev. The problems of Abai’s translations of excerpts from Pushkin’s works in domestic literary criticism were studied before by A.S. Kalmurzaev, K Zhumaliev, Sh. Eleukenov, S. Fomichev, G. Belger. We consider Abay’s reception of Pushkin’s hero, the influence of Pushkin’s artistic style on the Kazakh poet when displaying the everyday conflict and psychology generated by the influence of the environment and social relations, the relationship between a man and a woman. The reader’s attention is focused on the features of the socio-historical development of the Kazakh society, the national picture of the world, the individual talent of the akyn. The general and individual in the psychological display, reproduction of the image of Onegin in the artistic style of A.S. Pushkin and Abai Kunanbaev are analyzed. It is assumed that the comparison of the artistic styles of the two classics will contribute to the knowledge of the creative individuality, the uniqueness of the Kazakh genius.